Perception of acupuncture among users and nonusers: A qualitative study. Issue 1 (2nd January 2016) - Chan, Kara; Siu, Judy Yuen-man; Fung, Timothy K. F.
ABSTRACT: This study uses a qualitative methodology to examine the perception of acupuncture among users and nonusers. Altogether 37 participants, age 35 or older, were interviewed. Participants' perception of advantages and disadvantages of adopting acupuncture, and their criteria in selecting acupuncturists, were collected. Results found that among the user group, acupuncture was perceived as being effective, having little side effects, and generating lasting impact. Among nonusers, acupuncture was perceived as lacking a clinical base, high risk, and nonstandardized. Nonusers had less confidence in acupuncture than biomedicine. Participants relied on social communication and the practitioner's professional qualifications in choosing acupuncturists. Marketing implications are discussed.